Redox Modification of the Iron-Sulfur Glutaredoxin GRXS17 Activates Holdase Activity and Protects Plants from Heat Stress . Issue 2 (21st August 2020) - Martins, Laura; Knuesting, Johannes; Bariat, Laetitia; Dard, Avilien; Freibert, Sven A.; Marchand, Christophe H.; Young, David; Dung, Nguyen Ho Thuy; Voth, Wilhelm; Debures, Anne; Saez-Vasquez, Julio; Lemaire, Stéphane D.; et al.
Abstract : A Cys-dependent redox modification of the iron-sulfur cluster glutaredoxin GRXS17 activates its holdase activity and protects plants from heat stress. Abstract: Heat stress induces misfolding and aggregation of proteins unless they are guarded by chaperone systems. Here, we examined the function of the glutaredoxin GRXS17, a member of thiol reductase families in the model plant Arabidopsis ( Arabidopsis thaliana ). GRXS17 is a nucleocytosolic monothiol glutaredoxin consisting of an N-terminal thioredoxin domain and three CGFS active-site motif-containing GRX domains that coordinate three iron-sulfur (Fe-S) clusters in a glutathione-dependent manner. As an Fe-S cluster-charged holoenzyme, GRXS17 is likely involved in the maturation of cytosolic and nuclear Fe-S proteins. In addition to its role in cluster biogenesis, GRXS17 presented both foldase and redox-dependent holdase activities. Oxidative stress in combination with heat stress induced loss of its Fe-S clusters followed by subsequent formation of disulfide bonds between conserved active-site cysteines in the corresponding thioredoxin domains. This oxidation led to a shift of GRXS17 to a high-molecular-weight complex and thus activated its holdase activity in vitro. Moreover, GRXS17 was specifically involved in plant tolerance to moderate high temperature and protected root meristematic cells from heat-induced cell death. Finally, GRXS17 interacted with a different set of proteins upon heat stress, possibly protecting them from heat injuries. Therefore, we propose that the Fe-S cluster enzyme GRXS17 is an essential guard that protects proteins against moderate heat stress, likely through a redox-dependent chaperone activity. We reveal the mechanism of an Fe-S cluster-dependent activity shift that converts the holoenzyme GRXS17 into a holdase, thereby preventing damage caused by heat stress.